What are you hungry for? : the Chopra solution to permanent weight loss, well-being, and lightness of soul - Chopra, Deepak. frey50
"The New York Times bestselling author of Reinventing the Body, Resurrecting the Soul returns to his health and wellness roots with an exciting new approach to weight loss that focuses on the hungers we experience physically, mentally, and spiritually"--
Awareness and weight loss. Why this will work for you ; The mind-body connection -- The Chopra solution. change your story, change your body ; Purity, energy, and balance ; "What should I eat?" The Ayurvedic way ; The six tastes at every meal ; Expanded flavors ; The earliest prevention -- Raising your consciousness. The joy of awareness ; Self-regulation : let your body take care of you ; Emotional well-being : it's a choice ; Lightness of soul -- Recipes from the Chopra Center kitchen. Light breakfast ; Appetizers ; Soups ; Entrees and side dishes ; Salads ; Condiments, dips, and sauces ; Desserts ; Beverages.
Keywords: Weight loss; Mind and body; Medicine, Ayurvedic; Heath & Fitness / Diets; Health & Fitness / Healing; Self-Help / Spiritual; Cookbooks